PENGARUH KEBERADAAN UNIMUS TERHADAP EKONOMI MASYARAKAT SEKITAR DAN KONSTRIBUSINYA TERHADAP PEREKONOMIAN SEMARANG - Setia Iriyanto; Setia Budhi Wilardjo (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
The aim of this study was to investigate and analyze the economic development of the surrounding communities, after standing UNIMUS campus and to identify and analyze the economic development of Semarang after UNIMUS established, as part UNIMUS contribution to theeconomy of the city of Semarang. This study was conducted in the area around Campus Campus I and II UNIMUS were operational in 2006 at the Village Kedungmundu which is administratively located in the District of Tembalang, Semarang. Primary data collected are public economic dataaround campus UNIMUS Kedungmundu the number of respondents is 100 (with a method / formula Slovin, because the population is aplenty). Sampling was done by using purposive random sampling. While secondary data collected includes economic data the city, especially during thelast 5 years, from 2008 to 2014, while analyzing the data used Descriptive analysis and Econometric analysis using regression model as follows: Yi = β0 + β1X1i + β2X2i + β3 X3i + β4X4i + β5X5i + β6D1i + β7D2i + β8D3i + ei Keywords: Unimus, economic communities, the economy semarang.